Comorbidity variation in patients with obsessive-compulsive disorder according to symptom dimensions: Results from a large multicentre clinical sample - Torres, Albina R. [UNESP] (2016)
Background: Obsessive-compulsive disorder (OCD) has a heterogeneous and complex phenomenological picture, characterized by different symptom dimensions and comorbid psychiatric disorders, which frequently co-occur or are replaced by others over the illness course. To date, very few studies have investigated the associations between specific OCD symptom dimensions and comorbid disorders. Methods: Cross-sectional, multicenter clinical study with 1001 well-characterized OCD patients recruited within the Brazilian Research Consortium on Obsessive-Compulsive and Related Disorders. The primary instruments were the Dimensional Yale-Brown Obsessive Compulsive Scale (DY-BOCS) and the Structured Clinical Interview for DSM-IV Axis I Disorders. Bivariate analyses between symptom dimensions and comorbidities were followed by logistic regression. Results: The most common comorbidities among participants (56.8% females) were major depression (56.4%), social phobia (34.6%), generalized anxiety disorder (34.3%), and specific phobia (31.4%). The aggressive dimension was independently associated with posttraumatic stress disorder (PTSD), separation anxiety disorder, any impulse-control disorder and skin picking; the sexual-religious dimension was associated with mood disorders, panic disorder/agoraphobia, social phobia, separation anxiety disorder, non-paraphilic sexual disorder, any somatoform disorder, body dysmorphic disorder and tic disorders; the contamination-cleaning dimension was related to hypochondriasis; and the hoarding dimension was associated with depressive disorders, specific phobia, PTSD, impulse control disorders (compulsive buying, skin picking, internet use), ADHD and tic disorders. The symmetry-ordering dimension was not independently associated with any comorbidity. Limitations: Cross-sectional design; participants from only tertiary mental health services; personality disorders not investigated. Conclusions: Different OCD dimensions presented some specific associations with comorbid disorders, which may influence treatment seeking behaviors and response, and be suggestive of different underlying pathogenic mechanisms. (C) 2015 Elsevier B.V. All rights reserved.